2019
DOI: 10.1002/uog.19198
|View full text |Cite
|
Sign up to set email alerts
|

Binder syndrome: a phenotype rather than a definitive diagnosis?

Abstract: Binder's Syndrome is a congenital malformation characterized by nasomaxillary hypoplasia. It can be isolated or associated with multiple aetiologies, such as maternal intake of coumarin-based anticoagulants during pregnancy, systemic lupus erythematosus and some other monogenic conditions, such as Keutel syndrome or Chondrodysplasia punctata (CDP). [1] This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Genetic disorders associated with vitamin K deficiency include autosomal recessive vitamin K epoxide reductase deficiency, X-linked recessive form of CDP, and Xp22.3 deletion. [8][9][10][11][12] Sheffield et al 13 suggested that the BP represents a mild form of CDP and reported 103 cases of CDP in a 20-year examination period. However, in our case series, we could not identify any CDP cases.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic disorders associated with vitamin K deficiency include autosomal recessive vitamin K epoxide reductase deficiency, X-linked recessive form of CDP, and Xp22.3 deletion. [8][9][10][11][12] Sheffield et al 13 suggested that the BP represents a mild form of CDP and reported 103 cases of CDP in a 20-year examination period. However, in our case series, we could not identify any CDP cases.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is still unclear because it can also occur sporadically. It has been linked to use of coumarin-based anticoagulants during pregnancy and systemic lupus erythematosus ( Mazzone et al, 2019 ). The essential features of Binder's syndrome include a short nose, with a flattened nasal bridge, atrophy of the nasal mucosa, and aplastic frontal sinus and a tendency to develop Class III malocclusion and reverse overbite ( Heo and Jin, 2018 ).…”
Section: Syndromic Lesions Associated With Craniofacial Complexmentioning
confidence: 99%
“…1 The current understanding is that BS is not a disease but rather a phenotype with several causes. 2 BS is characterized by a shortened nose with a depressed nasal bridge, flat facies, and a convex upper lip. Malocclusion, underdevelopment of frontal sinus (FS), and anomalies of the cervical spine may be present.…”
Section: Introductionmentioning
confidence: 99%